Exploring the newer oxadiazoles as real inhibitors of human SIRT2 in hepatocellular cancer cells. Issue 16 (15th August 2020) - Dukanya,; Shanmugam, Muthu K.; Rangappa, Shobith; Metri, Prashant K.; Mohan, Surender; Basappa,; Rangappa, Kanchugarakoppal S.
Graphical abstract: Abstract: A novel series of indazole tethered oxadiazoles (OTDs) derivatives were synthesized, characterized and screened for their anti-proliferative activity against hepatocellular carcinoma (HCC) cells. OTDs structure was further confirmed by Single-crystal X-ray diffraction studies. Among the tested OTDs, compound 2-(4-methoxyphenyl)-5-(1-methyl-1H-indazol-3-yl)-1, 3, 4-oxadiazole was found to inhibit the catalytical activity of SIRT2 and brings about apoptosis as shown by western blot analysis and flow cytometry data. Also, the tested OTDs were found to interact with the active site of human SIRT2 in silico but not with the cavity of co-crystal ligand 5-(3- hydroxypropyl)-3-(4-chlorophenyl)-1, 2, 4-oxadiazole, which indicate that these OTDs has potential in the development of SIRT2 inhibitors in liver cancer models.